Notas Acerca da Pedagogia - Débora Mazza (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This paper is an approach of the scientific identity of Pedagogy while a Knowledgement field that deals with the educational theory and practice. It inserts the construction of the Pedagogic Theory in the interface with the disciplines of specific contents, with the areas that give them epistemological support, and with the amplification of the pedagogical spaces in the actual society.